THE EFFECT OF SHARIA COMPLIANCE, SERVICE QUALITY, PRODUCT QUALITY, AND ELECTRONIC WORD OF MOUTH ON CUSTOMER DECISIONS TO USE WADIAH PRODUCTS AT INDONESIAN SHARIA BANK (A CASE STUDY OF BSI AMBOKEMBANG BRANCH OFFICE) - Rizkiana, Rosita; Drajat Stiawan (UIN Raden Mas Said Surakarta, 2023)
The aim of the research is to determine the effect of sharia compliance, service quality, product quality, and electronic word of mouth on customers' decisions to use Wadiah at BSI Ambombang products. This research was field research with a descriptive quantitative approach. Data were obtained by distributing questionnaires to customers who use Wadiah products. The sampling technique was purposive sampling, which obtained 97 respondents. The data analysis techniques used instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination tests. The results show that the service quality, product quality, electronic word of mouth variable have a positive and significant influence on the customer's decision and the sharia compliance variable has a negative and significant effect on customers' decisions.